2009
DOI: 10.1051/0004-6361/200913021
|View full text |Cite
|
Sign up to set email alerts
|

Radio and spectroscopic properties of miniature radio galaxies: revealing the bulk of the radio-loud AGN population

Abstract: We explore radio and spectroscopic properties of a sample of 14 miniature radio galaxies, i.e. early-type core galaxies hosting radioloud AGN of extremely low radio power, 10 27−29 erg s −1 Hz −1 at 1.4 GHz. Miniature radio galaxies smoothly extend the relationships found for the more powerful FR I radio galaxies between emission line, optical and radio nuclear luminosities to lower levels. However, they have a deficit of a factor of ∼100 in extended radio emission with respect to that of the classical example… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 67 publications
6
93
0
Order By: Relevance
“…They find a lower limit of 0.86 for unresolved sources. Column (14): FR is the Fanaroff-Riley type at low frequency (1.4 GHz) (Fanaroff & Riley 1974;Baldi & Capetti 2009;Ghisellini 2011). …”
Section: Columns (2) and (3)mentioning
confidence: 99%
“…They find a lower limit of 0.86 for unresolved sources. Column (14): FR is the Fanaroff-Riley type at low frequency (1.4 GHz) (Fanaroff & Riley 1974;Baldi & Capetti 2009;Ghisellini 2011). …”
Section: Columns (2) and (3)mentioning
confidence: 99%
“…The lack of clear starburst regions in the optical HST images (Capetti & Balmaverde 2005) and no evidence of young stellar populations in their optical spectra (Baldi & Capetti 2009) rule out a star formation origin for these trends. A reasonable, but not obvious, explanation of the trends might be the most basic mechanism of heating of the molecular clouds by high-energy photons (e.g., UV and X-ray photons) from the AGN, as suggested by Braine & Combes (1992).…”
Section: Molecular Gas and Nuclear Propertiesmentioning
confidence: 98%
“…These studies show that the two optical classes of objects correspond to different AGN properties. On one hand, the CoreG represent "miniature radio galaxies", i.e., a scaled-down version of FR Is (Baldi & Capetti 2009). They invariably host RL nuclei, spectroscopically classified as low-excitation galaxies, with an average radio-loudness parameter of R = L 5 GHz /L B ∼ 4000, similarly to FR Is.…”
Section: Sample Observations and Datamentioning
confidence: 99%
“…the 2 Jy (Morganti et al 1997;Tadhunter et al 1998) follow relations between radio and line emission similar to the 3CR. Baldi & Capetti (2009) showed that a large ratio of line emission to the radio power with respect to 3CR sources is characteristic of the radio-loud AGN selected by Best et al (2005). The latter authors cross-matched the ∼212 000 galaxies drawn from the SDSS-DR2 with the NVSS and FIRST 7 radio surveys, selecting a sample of 2215 radio-loud AGN (with a radio flux threshold of 5 mJy) to which we refer hereafter as the SDSS/NVSS sample.…”
Section: The Parent Populationmentioning
confidence: 99%
“…Moreover, they saw that HEG are associated with very powerful FR II only, while LEG are spread on a wide range of radio powers, and can be of both FR II and FR I type. Actually, the situation is even more complex, as the existence of miniature radio galaxies, characterized by extremely low radio power, relatively luminous narrow emission lines, and no BLR, demonstrates (Baldi & Capetti 2009). …”
Section: Introductionmentioning
confidence: 99%